Toleransi: Peran Tokoh Agama sebagai Perekat Kerukunan Umat Beragama - Samuel, Samuel; Tumonglo, Esther Epin (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
Religious Figures As Adhesives for Inter-religious Harmony in Toraja, starting from the phenomenon that the Toraja people, specifically the southern Toraja bordering the Enrekang area, which is predominantly Muslim, is a plural society from generation to generation while maintaining harmony between religious communities, especially Christian Muslims. This harmony has never been shaken by sara issues like in some other places. One of the glues is the religious leaders themselves. As the focus of this research, a research question was formulated, namely how religious figures play a role in gluing harmony between religious communities. These problems are studied using the theory of pluralism. Meanwhile, for field data, qualitative research methods were used, namely by observing with the aim of obtaining information about how the role of religious leaders in gluing inter-religious harmony. As a research finding, the role of religious leaders in gluing tolerance between religious communities, especially Christian Muslims in Toraja, is that religious leaders are able to act as role models or role models, coaches and are able to act as leaders for every community.ABSTRAKTokoh Agama Sebagai Perekat Kerukunan Antar Umat Beragama di Toraja, bertitik tolak dari fenomena bahwa masyarakat Toraja secara khusus Toraja bagian selatan yang berbatasan dengan daerah Enrekang yang mayoritas muslim adalah masyarakat majemuk dari turun temurun tetap memelihara kerukunan antar umat beragama khususnya Islam Kristen. Kerukunan tersebut tidak pernah tergoyahkan oleh isu-isu sara seperti di beberapa tempat lainnya. Salah satu perekat adalah tokoh agama sendiri. Sebagai focus penelitian ini dirumuskan question research yaitu bagaimana Tokoh Agama berperan dalam merekatkan kerukunan antar umat beragama. Permasalahan tersebut dikaji dengan menggunakan teori pluralisme. Sementara untuk data lapangan digunakan metode penelitian kualitatif yaitu dengan mengamati dan juga melalui wawancara bersama informan dengan tujuan untuk memperoleh informasi tentang peran tokoh agama dalam merekatkan kerukunan antar umat beragama. Sebagai temuan penelitian bahwa peran tokoh agama dalam merekatkan toleransi antar umat beragama khususnya Kristen Islam di Toraja adalah tokoh agama mampu berperan sebagai teladan atau panutan, Pembina serta mampu berperan sebagai pemimpin bagi setiap uma